Inoperable patients with acute type A dissection: are they candidates for endovascular repair?. (18th July 2017) - Roselli, Eric E.; Hasan, Saad M.; Idrees, Jay J.; Aftab, Muhammad; Eagleton, Matthew J.; Menon, Venu; Svensson, Lars G.
Abstract: OBJECTIVES: The objectives are to (i) report characteristics and outcomes of patients with inoperable acute type A aortic dissection, (ii) describe proximal aortic morphology and (iii) identify potential for endovascular treatment of the entry tear. METHODS: Fifty-three (7.7%) of 686 patients with acute type A dissection between 2005 and 2015 were deemed inoperable. Chart review and active follow-up were performed for clinical characteristics and outcomes. Specific attention was directed at determining the reasons for inoperability. Twenty-four patients had computed tomography scans available for 3D reconstruction and imaging analysis. Measurements included diameter and cross-sectional area at multiple levels; plus lengths along the centreline, greater and lesser curves and outer wall of dissection. The entry tear location was identified. Entry tears between the sinotubular junction and innominate artery, or distal to the left subclavian artery, were considered amenable to endovascular repair. RESULTS: The reasons for inoperability were characterized as very high-risk 35 (66%) or prohibitive 18 (34%). Prohibitive risk factors included dementia, severe stroke, malperfusion and advanced malignancy. Thirty-day mortality occurred in 35 (66%). On imaging analysis, the sinotubular junction was <45 mm in 18 (75%). The false lumen was located along the greater curve in 16 (67%), lesser curve 2 (8%), anteriorly in 5 (21%) and posteriorly in 1 (4%). The entry tear was potentially amenable to coverage in 19 (79%) patients—between the sinotubular junction and innominate artery in 18 patients and distal to the left subclavian artery in 1 patient. The entry tear was in the aortic root and arch in 1 patient (4%) each and not visible in 3 patients (13%). CONCLUSIONS: Only one-third of inoperable patients are prohibitive risk for any intervention. The entry tears in most patients are potentially coverable with endovascular devices. Additional imaging and engineering analysis will guide the design of disease specific devices.